ACUTE KIDNEY INJURY: HISTORICAL ASPECTS AND DIAGNOSTIC CRITERIA - J. V. Kopylova; Y. L. Poz; A. G. Strokov; V. N. Poptsov; O. V. Voronina; S. G. Uhrenkov (Вестник трансплантологии и искусственных органов, 2010)
The in-depth review is dedicated to the acute kidney injury. This conception is wider than acute renal failure. Even minor decline of renal function bias outcomes, so early diagnosis of acute renal injury is exceedingly important. The new markers of kidney injury are actively investigated. RIFLE criteria provide universal approach to a problem at first, and allow comparison of study results at second.